Descriptive analysis of the effect of back protector on the prevention of vertebral and thoracolumbar injuries in serious motorcycle accident. (February 2020) - Afquir, Sanae; Melot, Anthony; Ndiaye, Amina; Hammad, Emmanuelle; Martin, Jean-Louis; Arnoux, Pierre-Jean
Abstract: Context and objective: Among the different products and protective gear used by riders of two-wheeled motorized vehicles, back protectors that are designed to prevent damage to the spinal column are widely used today compared other protections. However, few studies measure their effectiveness. Can their effectiveness be measured? How do they help decrease or change the nature of thoracolumbar traumas that occur? To address these questions and remedy the lack of objective data regarding these products, an epidemiological, clinical, and biomechanical analysis of motorcycle riders who were admitted to a French trauma center after an accident was performed. So, this study investigates the effectiveness of back protectors, including their ability to prevent specific mechanisms of thoracic and lumbar spinal injuries related to TWMV accidents. Method: A questionnaire was administered to victims of accidents involving two-wheeled motorized vehicles who were admitted to the trauma room at the Marseille trauma center over the course of 2016. Collect data are related to the victim, the accident scenario, and a detailed description of the observed injuries using AIS (Abbreviated Injury Scale) coding and Magerl classification. Univariate analyses and Fisher tests were performed for victims who were or were not wearing back protectors. Results: This study collected data from 124 victims. Almost half of the victims were wearing a back protector at the time of the accident (53 victims, thus 43% of riders). Collectively, twenty-nine victims who were wearing back protectors had 57 thoracolumbar injuries, and twenty eight victims who were not wearing back protectors had 75 thoracolumbar lesions. The results from this study show that there is no significant difference in the nature and mechanism of thoracolumbar injuries as a function of back protection. The majority of the thoracolumbar injuries were not severe. They were primarily bone injuries, essentially compression fractures, regardless of whether a back protector was worn. Conclusion: This study shows that the use of back protection does not decrease the number, type, or mechanism of thoracolumbar injuries associated with accidents involving two-wheeled motorized vehicles. However, it suggests that lumbar vertebral injuries are deflected towards the thoracic vertebrae when back protectors are worn. Finally, it suggests that the design of back protectors should be reconsidered to better protect riders from what are referred to as compression fractures (craniocaudal force), which remain the primary form of fracture regardless of the rider's characteristics, based on the data analyzed.